Strategi Pengembangan Pemasaran â€œKamsia Bobaâ€ Sebagai Salah Satu Produk UMKM di Tambun Selatan - Resti Meliana Putri; Tyna Yunita; Alfia Dwi Cahyani; Indra Samuel (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Nowadays, various brands and types of viral drinks continue to emerge in Indonesia. Boba drink is one of those kinds of popular drinks, which originated from Taiwan and has become a popular beverage throughout the world, including in Indonesia, especially among youths and young adults. Boba drink contains high levels of sugar and calorie and is part of the larger group of sugarsweetened beverage (SSB). Boba shops generally offer various beverage flavors, toppings, sizes, choices of sugar and ice level that can be personalized. . The